2017
DOI: 10.1002/cpp.2118
|View full text |Cite
|
Sign up to set email alerts
|

Resilience to suicide ideation: A cross‐cultural test of the buffering hypothesis

Abstract: Depression and suicide ideation are common in student populations across the world. The present study investigated factors buffering the association between depression and suicide ideation. A total of 2,687 Chinese students and 601 German students took part in the investigation. Social support, satisfaction with life, self-efficacy, psychosocial stress resistance, and positive mental health were considered as resilience factors moderating the association between depressive symptoms and suicide ideation within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
54
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 46 publications
7
54
0
3
Order By: Relevance
“…Positive mental health, psychological well‐being, and self‐acceptance—a facet of psychological well‐being—moderated the impact of entrapment on suicide ideation: Individuals who reported low levels of positive mental health, psychological well‐being, and/or self‐acceptance were particularly likely to suffer from suicide ideation at higher levels of entrapment. The current study complements previous research showing an association between entrapment and suicide ideation (Siddaway et al, ) as well as between PMH and suicide ideation (Siegmann et al, , ; Teismann, Forkmann, et al, ). These results provide support for the IMV‐Model (O'Connor, ; O'Connor & Kirtley, ): According to the IMV‐model, the presence of motivational moderators renders it more or less likely that entrapment translates into suicide ideation.…”
Section: Discussionsupporting
confidence: 90%
“…Positive mental health, psychological well‐being, and self‐acceptance—a facet of psychological well‐being—moderated the impact of entrapment on suicide ideation: Individuals who reported low levels of positive mental health, psychological well‐being, and/or self‐acceptance were particularly likely to suffer from suicide ideation at higher levels of entrapment. The current study complements previous research showing an association between entrapment and suicide ideation (Siddaway et al, ) as well as between PMH and suicide ideation (Siegmann et al, , ; Teismann, Forkmann, et al, ). These results provide support for the IMV‐Model (O'Connor, ; O'Connor & Kirtley, ): According to the IMV‐model, the presence of motivational moderators renders it more or less likely that entrapment translates into suicide ideation.…”
Section: Discussionsupporting
confidence: 90%
“…Earlier research repeatedly emphasized the protective effect of PMH in different populations. For example, in a cross-sectional study as well as in a longitudinal study, PMH was found to buffer the effect of depression symptoms on suicide ideation in student samples (Siegmann et al, 2017;Teismann, Forkmann, et al, 2018). In a further student sample, PMH significantly mediated the impact of cyberbullying on suicide ideation and suicide behavior (Brailovskaia, Teismann, & Margraf, 2018a).…”
Section: Introductionmentioning
confidence: 92%
“…Depression and hopelessness seem to present an additional risk, as does low self-esteem [58]; in contrast, psychological factors such as attribution style, self-forgiveness, and feelings of agency may confer resilience [59][60][61]. Social support, or indeed perceived social support, also decreases the risk of self-injury turning to suicide attempts [62]. Parental support especially reduces the likelihood of suicide attempts in young self-harmers [16,58], and appears to be further helpful in moderating the likelihood that bullied individuals will self-injure [63].…”
mentioning
confidence: 99%